2021
DOI: 10.14786/flr.v9i2.647
|View full text |Cite
|
Sign up to set email alerts
|

Predicting freshmen’s academic adjustment and subsequent achievement: differences between academic and professional higher education contexts

Abstract: This study tests an integrative model, which delineates how students’ academic motivation, academic self-efficacy and learning strategies (processing strategies and regulation strategies) at the end of secondary education impact academic adjustment in the first semester of the first year of higher education (FYHE) and subsequent academic achievement at the end of the FYHE, in two types of HE programmes. More precisely, the present study explores the extent to which the explanatory values of aforementioned dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
(93 reference statements)
1
7
0
6
Order By: Relevance
“…This suggests that even though students are enrolled in a different academic environment, the configuration of emotional anticipation is the same for both groups. Although prior research has already examined university and college students’ differences about the academic adjustment to the transition to higher education (Willems et al., 2021), this is the first study that compared the differences in emotional processes among the two educational contexts. From a practical perspective, the present findings represent an important step in relation to students’ emotional anticipation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that even though students are enrolled in a different academic environment, the configuration of emotional anticipation is the same for both groups. Although prior research has already examined university and college students’ differences about the academic adjustment to the transition to higher education (Willems et al., 2021), this is the first study that compared the differences in emotional processes among the two educational contexts. From a practical perspective, the present findings represent an important step in relation to students’ emotional anticipation.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy can also be considered important in developing life-long learning. Willems et al (2021) showed in their research that students' self-efficacy was positively associated with academic adjustment. It had a positive impact on academic achievement, both directly and indirectly, through academic adjustment.…”
Section: Developing a Greater Focus On 21 St Century Life-long Activementioning
confidence: 99%
“…Finally, they found that contextual differences predicted about 15 percent of academic achievement, but that this was different depending on students' study programs. Willems et al (2021) also considered differences between academic programmes and professional programmes. They found that learning strategies and motivational variables at the end of secondary education were more predictive for students' first-year adjustment in the academic programmes than in professional programmes.…”
Section: Supporting First-year and Ongoing Transition Through Developmentioning
confidence: 99%
“…The study's three-wave longitudinal design allows the researchers to analyse changes within individuals, differences between students and interaction effects between them. Similarly, Willems et al (2021) conduct SEM analyses on a longitudinal dataset to explore to what extent students' psychosocial variables at the end of secondary education can predict their academic achievement and adjustment during the first year at university. It is novel here that the authors also investigate whether the predictive power might differ depending on whether students are enrolled in professional or academic programs.…”
Section: Moving Beyond Single-factor Analysis Of Student Transitionsmentioning
confidence: 99%
“…The difficulty in separating micro-from meso-level variables without acknowledging their interdependence can be further illustrated by the research of Willems et al (2021). The authors frame diversity at the meso level as 'programme diversity', pointing to differences especially between academic and professional disciplines with regard to their aims, conditions and teaching methods.…”
Section: The Distinction Between Micro Meso and Macro Levels In Transition Researchmentioning
confidence: 99%